2014
DOI: 10.1111/j.2047-2927.2014.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Testicular cancer and sperm DNA damage: short‐ and long‐term effects of antineoplastic treatment

Abstract: SUMMARYThe aim of this study was to investigate sperm DNA damage induced by chemo-and radiotherapy in patients with testicular cancer to provide data on the extent and persistence of nuclear damage that might affect individual reproductive potential. We evaluated pre-and post-antineoplastic treatment sperm DNA integrity, expressed as DNA Fragmentation Index (DFI), in a large caseload of testicular cancer patients by sperm chromatin structure assay. The mean total DFI for all patients at T0 was 18.0 AE 12.5%. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 29 publications
9
34
0
1
Order By: Relevance
“…Another important finding from our current study is the lack of recovery of radiotherapyinduced sperm DNA damage seen in patients with the hMSH5 C85T variant. It has been observed that sperm from infertile men often contain more DNA damage -a likely contributing factor for poor reproduction (Zini et al, 2001;Paoli et al, 2015). A potentially intriguing observation of our current study is the higher pretreatment sperm counts in the CT + TT group of TGCT patients.…”
Section: Discussionsupporting
confidence: 54%
“…Another important finding from our current study is the lack of recovery of radiotherapyinduced sperm DNA damage seen in patients with the hMSH5 C85T variant. It has been observed that sperm from infertile men often contain more DNA damage -a likely contributing factor for poor reproduction (Zini et al, 2001;Paoli et al, 2015). A potentially intriguing observation of our current study is the higher pretreatment sperm counts in the CT + TT group of TGCT patients.…”
Section: Discussionsupporting
confidence: 54%
“…Another study of chromatin integrity in 21 infertile and 15 postorchiectomy TGCT patients who were to undergo chemotherapy found mean DFI values (assessed by SCSA) to be significantly higher in both the infertile (22%) and TGCT patients (15%) in comparison to healthy controls (8%) [28]. Paoli et al [29] report a mean DFI score of 18.0 ± 12.5% in a group of 131 postorchiectomy TGCT patients awaiting chemotherapy (assessed by SCSA). Similarly, Spermon et al [30] report the median percentage of damaged sperm cells (assessed by TUNEL) to be 21% in postorchiectomy TGCT patients awaiting chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Raised DNA fragmentation, as quantitated by the DNA fragmentation index (DFI), is associated with decreased conception rates and early pregnancy loss . Paoli et al found that after chemotherapy DFI increases significantly 3 months post chemotherapy. At this time point, men had a mean DFI of 28% after one to two cycles of BEP, and 33% after three to four cycles; however, DFI returns to baseline after 9 months and there is a significant decrease at 12 and 24 months.…”
Section: Testicular Cancer Treatment and Infertilitymentioning
confidence: 99%